Healthcare Communicators And Instructors\' Administrative-Recreational Experiences In Breaking Off With The Headquarter: A Qualitative Study - Akram Bayati; Fatemeh Ghanbari; Mohsen Shamsi; Razieh Rajabi (Tehran University of Medical Sciences, 2013)
Background and Aim: Regarding the importance of communicators' presence in health programs and the fact that in recent years, we have witnessed a decrease in their cooperation or a cut in their relationship with the headquarters. This qualitative study was performed to clarify communicators and instructors' administrative-recreational experiences in breaking off with the headquarters. Materials and Methods: This qualitative study was carried out on 60 healthcare communicators, 20 ex- communicators and 35 instructors selected through purposive sampling. The data were collected using focus discussion groups and semi-structured interviews with the participants. For data analysis, qualitative content analysis was employed. Results: The findings of data analysis revealed two main levels: recreational and administrative. The key themes of the former included medical facilities, gifts, employment, futurism and camp and of the latter consisted of credit resources, instructors' conditions, organizational posts and orientation. Conclusion: Expressing what is expected from communicators when selecting them can play a significant role in keeping them up with their jobs. Holding meetings between authorities and communicators' representatives to discuss their problems and present solutions, holding reward ceremonies, preparing the grounds for attracting financial resources to support communicators' programs, appreciating them and enhancing the communicators and instructors' academic level, and creating organizational posts for instructors can be effective in maintaining their presence and enhancing health communicators' program.